2011
DOI: 10.1093/brain/awr178
|View full text |Cite
|
Sign up to set email alerts
|

White matter alterations differ in primary lateral sclerosis and amyotrophic lateral sclerosis

Abstract: Primary lateral sclerosis is a sporadic disorder characterized by slowly progressive corticospinal dysfunction. Primary lateral sclerosis differs from amyotrophic lateral sclerosis by its lack of lower motor neuron signs and long survival. Few pathological studies have been carried out on patients with primary lateral sclerosis, and the relationship between primary lateral sclerosis and amyotrophic lateral sclerosis remains uncertain. To detect in vivo structural differences between the two disorders, diffusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
100
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(116 citation statements)
references
References 54 publications
13
100
0
1
Order By: Relevance
“…Involvement of the corpus callosum (CC) is a consistent feature of ALS [Filippini et al, 2010], thought to contribute to a functional impairment of interhemispheric inhibition, as evidenced by both TMS [Karandreas et al, 2007; Wittstock et al, 2007] and clinically evident mirror movements [Wittstock et al, 2011]. The CC appears to be a particularly vulnerable structure in PLS [Agosta et al, 2014; Ciccarelli et al, 2009; Iwata et al, 2011; Kolind et al, 2013] and a finding of delayed lateralization of PMBR is in keeping with this observation. Preserved hemispheric autonomy is still demonstrated by the time that PMBR peaks, suggesting still adequate CC functionality, although partial mirror movements during response epochs were also noted in some patients' EMG.…”
Section: Discussionmentioning
confidence: 99%
“…Involvement of the corpus callosum (CC) is a consistent feature of ALS [Filippini et al, 2010], thought to contribute to a functional impairment of interhemispheric inhibition, as evidenced by both TMS [Karandreas et al, 2007; Wittstock et al, 2007] and clinically evident mirror movements [Wittstock et al, 2011]. The CC appears to be a particularly vulnerable structure in PLS [Agosta et al, 2014; Ciccarelli et al, 2009; Iwata et al, 2011; Kolind et al, 2013] and a finding of delayed lateralization of PMBR is in keeping with this observation. Preserved hemispheric autonomy is still demonstrated by the time that PMBR peaks, suggesting still adequate CC functionality, although partial mirror movements during response epochs were also noted in some patients' EMG.…”
Section: Discussionmentioning
confidence: 99%
“…The affected regions included the subcortical white matter, internal capsule, and the corpus callosum, consistent with other studies. 26,28,29 In the second step, to identify white matter regions associated with PBA, white matter voxels that differed from controls were compared between PBA1 and PBA2 patients, with ALSFRS-R and diagnosis (ALS vs PLS) as covariates. This analysis revealed a small region of white matter underlying the left motor cortex with reduced FA in PBA1 compared with PBA2 patients ( figure 3, row A).…”
Section: Statistical Analysis Of Clinical Data Continuous Demographicmentioning
confidence: 99%
“…Voxel-wise statistical analysis of the FA skeletons was performed using tract-based spatial statistics (version 1.2; http://www.fmrib.ox.ac.uk/fsl/), 25 with methods previously described. 26 Imaging analysis. A 2-step process was used to identify white matter tracts associated with PBA.…”
mentioning
confidence: 99%
“…32 However, it is perhaps surprising that DTI studies have not consistently demonstrated a relationship between FA (or MD) and disability (studies reviewed in reference 5). An apparent paradox has also emerged whereby higher FA values (thought to reflect greater WM tract integrity) have been noted in patients with the longest disease duration, 3,33 despite evidence of decreasing FA values in some, but not all longitudinal studies. 34,35 There are also data specifically supporting a role for baseline FA in prognostication.…”
Section: Dti Analysis the Diffusion Toolbox Of The Fmrib (Centre Formentioning
confidence: 99%